Sosialisasi Keselamatan Penyeberangan Wisata Pulau-Pulau Makassar - Firman Husain; Juswan -; Taufiqur Rachman; Ashury -; Muhammad Zubair Muis Alie; Habibi Palippui (Faculty of Engineering UNHAS, 2021)
The increasing number of tourists visiting the islands in the Makassar City area is an exciting thing, especially for the perpetrators of inter-island crossing transportation. On the other hand, the safety aspect of this crossing must be a concern not only for tourists and the crossing transportation actors themselves, but the government and the general public must also provide input. Currently, there are about 25 boats operating on island tourism crossings, especially those operating at Panyua Pier. To increase awareness and safety of this sea crossing, a socialization activity on safety rules was carried out. The socialization was carried out directly in the room by presenting the crossing transportation actors. The participants were given material on safety rules for sea crossing transportation by the socialization team from the Department of Marine Engineering as part of the tridharma of higher education. Due to the ongoing pandemic conditions, the number of participants present in the room is limited. This socialization activity is aimed at the perpetrators of crossing transportation to tourist islands or in local terms called